Paradise Kiddie Kindergarten / Nur Imannina Ibrahim ... [et al.] - Ibrahim, Nur Imannina; Shazali, Nur Ain Atirah; Abdul Rahman, Nur Azzah Syahirah; Burhaniza, Zaidatul Amira; Khamizan, Muhammad Fitri
Paradise Kiddie Kindergarten is an indoor playground for kids. It is located at The Spring in Kuching, Sarawak. It is difference from any playground. This is because, besides just being a playground, we also provide service such as school playground for kids which means kids can have modern teaching based technologies that provide . Since parents nowadays often busy with their work at the office. They can send their kids at Paradise Kiddie Kindergarten and this is the answer to an increasing demand.